Halal Value Chain Analysis in Poultry Slaughterhouse UD. Mandiri Bu Warni in Gambiran - Banyuwangi - Siti Nur Hafifatul Hasanah; Abdul Rokhim; Siti Masrohatin (Journal of Islamic Economy, 2025)
This study aims to analyze halal values ​​in the value chain of the UD Poultry Slaughterhouse industry. Independent Mrs. Warni. The methods used in this research include direct observation, interviews, and document analysis related to the production process. The results showed that UD. Mandiri Bu Warni has carried out the process well, starting from the supply of chicken, halal slaughter, to delivery to consumers. However, UD. Mandiri has not fully maintained the purity of chicken meat, because it is only cleaned with water to make it look clean. In addition, UD. Mandiri Bu Warni also has not used packaging that has a halal label, even though it already has a halal certificate which is currently still in the process of being extended. Therefore, this research contributes to the development of the Poultry Slaughterhouse industry by applying the value chain and halal principles